P748 Retrospective study on incidence rates of NAFLD and advanced liver fibrosis in Crohn's disease and ulcerative colitis. (25th January 2019) - Domislovic, V; Knezevic Stromar, I; Premuzic, M; Vranesic Bender, D; Matasin, M; Milinkovic, A; Mikolasevic, I; Krznaric, Z
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at higher risk for non-alcoholic fatty liver disease (NAFLD) compared with general population. Complex pathogenesis of NAFLD in IBD may be related to disease-specific risk factors such as chronic inflammation, steroid exposure, drug-induced hepatotoxicity, malnutrition and alteration of gut microbiota, major emerging factor in the pathogenesis of NAFLD. The goal of the study was to compare incidence rates (IR) of NAFLD and advanced liver fibrosis (ALF) in patients with CD and UC. Methods: This is a retrospective study on IBD patients without extra-intestinal manifestations and known liver disease. NAFLD was defined as Hepatic Steatosis Index (HSI) ≥36, and ALF was defined as FIB-4 ≥2.67. Active CD was defined using Harvey–Bradshaw Index ≥5 during follow-up. Incidence and predictors of NAFLD development were analysed using Kaplan–Meier and Cox regression analyses. Results: In this retrospective study we included 250 IBD patients; 167 patients with CD and 83 patients with UC (median age 40 yr, 52.2% males) that were observed for a median of 4.6 years. During 639 persons-year (PY) in CD group, 61 (36.5%) patients developed NAFLD (IR 9.5/100 PY (95% CI, 7.3–12.2)). In UC patients over 212 PY, 30 (36.1%) developed NAFLD (IR 14.1/100 PY (95% CI, 9.5–20). When analysing liver fibrosis, over a 860 PY in CD group, 5 (2.9%) patients developed ALF (IR 0.6/100 PY (95% CI, 0.2–1.3), and over a 386 PY in UC Group 4 (4.8%) patients developed ALF (IR 1/100 PY (95% CI, 0.2–2.6). There was no difference between CD and UC in incidence rates of NAFLD ( p = 0.07) and ALF ( p = 0.38). Development of NAFLD in CD was predicted by disease activity (HR 1.47; 95% CI 1.05–2.1; p < 0.05) and disease duration (HR 1.45; 95% CI 1.06–1.8; p < 0.05), while in UC was predicted by disease activity (HR 1.67; 95% CI 1.2–2.4; p < 0.05). Conclusions: NAFLD is frequent comorbidity in patients with CD and UC, which can lead to development or advanced liver fibrosis. Our results show that there is no difference in incidence rates of NAFLD and advanced liver fibrosis in different groups of IBD patients, even though there was a trend towards higher incidence rates of NAFLD in UC ( p = 0.07). Disease activity and duration of IBD are predictors of NAFLD development. This study points out the complexity of disease-specific risk factors and importance of better stratifications of IBD patients at risk of NAFLD and development advanced liver fibrosis.